2021
DOI: 10.1016/j.childyouth.2020.105906
|View full text |Cite
|
Sign up to set email alerts
|

The experience of social distancing for families with children and adolescents during the coronavirus (COVID-19) pandemic in Uruguay: Difficulties and opportunities

Abstract: Highlights The experiences of Uruguayan families during the COVID-19 pandemic were explored. The pandemic elicited negative feelings in the majority of participants. Social distancing measures caused a major disruption in daily habits. Changes in children's mood and behavior were perceived by the majority of the participants. Participants from low socio-economic level faced more difficulties to cope with social distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 25 publications
3
60
0
5
Order By: Relevance
“…Moreover, it is well known that the COVID-19 pandemic has created negative feelings such as anxiety, fear, worry, and uncertainty, and confronted many people with job loss, problems with unemployment insurance, compulsory unpaid leave, or the impossibility of working due to social distancing measures (Ares et al, 2021 ). As they do in usual times, teachers are taking families and children as a whole during the pandemic and continue to support families in this way.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is well known that the COVID-19 pandemic has created negative feelings such as anxiety, fear, worry, and uncertainty, and confronted many people with job loss, problems with unemployment insurance, compulsory unpaid leave, or the impossibility of working due to social distancing measures (Ares et al, 2021 ). As they do in usual times, teachers are taking families and children as a whole during the pandemic and continue to support families in this way.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…As one might expect, the negative conditions created by the COVID-19 pandemic are also true for teachers. Feeling emotionally tired, suffering from anxiety about keeping themselves and their family members safe or from grief over the loss of a close person, sensitively managing their relationships with their children at home as a parent, or lacking emotional interaction with colleagues, students, and friends might cause teachers to suffer from stress during this time (Soldatelli, 2020, as cited in Ares et al, 2021 ). It has been concluded in this study that one of educators’ basic needs during the COVID-19 pandemic is to ensure their psychological well-being.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…Accessed January 26, 2021. https://www.theguardian.com/world/2020/mar/18/coronavirus-lockdowneu-belgium-germany-adopt-measures restrictions across Europe varied significantly between the countries and should therefore lead to observed differences in the level of distress. Several studies show that the overall functioning deterioration rates and experienced stress levels during the COVID-19 outbreak are very high across the general population (Gualano et al, 2020;Pakenham et al, 2020;Pieh et al, 2020;Ares et al, 2021;Tan et al, 2021), and are associated, among others, with the loss of job and social support, fear of infection, change of lifestyle, and isolation (Dymecka et al, 2020). Still, little is known on predispositions to mental health deterioration and the presence of any possible protective factors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found two qualitative content analyses on comments, one from Singapore [ 7 ] and one from Uruguay [ 22 ]. Shorey et al [ 7 ] identified worries about what would happen to the affected businesses, virus transmitted through tourists and contracting the virus from colleagues and/or at public transportation.…”
Section: Introductionmentioning
confidence: 99%
“…Shorey et al [ 7 ] identified worries about what would happen to the affected businesses, virus transmitted through tourists and contracting the virus from colleagues and/or at public transportation. In Uruguay, Ares et al [ 22 ] identified worries about the health of family members, employment and the economic situation for oneself and the country.…”
Section: Introductionmentioning
confidence: 99%